Pengaruh Integrated Marketing Communication (IMC) terhadap Brand Equity pada PT.BPR Syariah Ampek Angkek Candung - Riri, Riri; Nurani, Khadijah (ARZUSIN, 2026)
Integrated Marketing Communication (IMC) has received attention in various studies, but research specifically examining the influence of advertising, sales promotion, public relations, direct marketing, personal selling, and event and experience on brand equity in Islamic banking institutions remains limited. This study aims to analyze the influence of IMC on brand equity at PT BPR Syariah Ampek Angkek Candung. This study used a quantitative approach with a survey design, involving 100 respondents selected through simple random sampling. Data were collected using a questionnaire and analyzed through multiple linear regression with the assistance of SPSS 22. The results showed that, simultaneously, advertising, sales promotion, public relations, direct marketing, personal selling, and event and experience had a significant effect on brand equity. Partially, advertising, public relations, direct marketing, and personal selling had a positive and significant effect on brand equity, whereas sales promotion and event and experience had no significant effect. The personal selling variable was the factor with the greatest influence on the company’s brand equity. The conclusion of this study affirms that integrated marketing communication plays an important role in strengthening brand equity in Islamic banking institutions. These findings contribute to the development of IMC studies and broaden understanding of marketing communication strategies in the Islamic banking sector, while also providing practical implications for the company to improve the effectiveness of sales promotion and event activities so as to strengthen customer loyalty and positive perceptions.